The diversity of plant species, the types of plant uses and the estimate of carbon stock in agroforestry system in Harapan Makmur Village, Bengkulu, Indonesia - WIRYONO WIRYONO; VENNY NOVIA UTAMI PUTERI; GUNGGUNG SENOAJI (Society for Indonesian Biodiversity, 2016)
Wiryono, Puteri VNU, Senoaji G. 2016. The diversity of plant species, the types of plant uses and the estimate of carbon stock in agroforestry system in Harapan Makmur Village, Bengkulu, Indonesia. Biodiversitas 17: 249-255. Homegardens are a traditional form of agroforestry commonly found in rural areas in Indonesia, where a variety of agricultural crops and forest trees are grown in a mixed system. To some extent, the traditional homegardens resemble natural forest in vegetation structure and composition. The objective of this study was to know the diversity of plant species, the types of plant uses and the estimate of carbon stock in homegardens in, Harapan Makmur Village, Central Bengkulu District, Bengkulu Province, Indonesia. The field work was conducted in 2013. The data of uses were collected through interview, while data on vegetation were gathered from measurement. The data were analyzed qualitatively and quantitatively. The results showed that 101 species of plants were found in the homegardens, with a Shannon-WienerÂ diversity index of 0.99 for trees. The most dominant species of trees was Hevea brasiliensis Willd (rubber tree) with an importance value index of 127 %. For saplings and shrubs, rubber was also the most dominant with 169 individuals, while for herbs, Agrostis sp. was the most dominant species with an average coverage of 25.8 %. The community used plants for several purposes: 41 species for food, 21 for fire wood, 13 for ornamental plants, 11 for medicines, 7 for construction wood, 6 for shade trees, 2 for handy craft, 4 for hedge, 3 for forage, and 2 for coloring. Twenty three species were not used. The estimate of carbon stock in trees was 95.2 ton ha-1. .